The Influence of Green Banking on Financial Inclusion and Sharia Banking Growth in Indonesia - Winsi Fadiah Putri; Bakhtiar Efendi; Rusiadi Rusiadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The banking industry has a very important role in a country's economy. One of the things related to the banking sector is operational activities towards the environment. The increasing environmental damage that occurs is a form of human indiscipline in managing natural resources. Therefore, efforts that banks can make to implement environmentally friendly practices in their operational activities are green banking by considering the 5P aspects, namely People, Planet, Partnership, Peace and Prosperity. Even though banks do not contribute directly to environmental pollution, sectors that carry out business activities cannot possibly operate if they do not have capital to finance their operations and one of the financial institutions that provides capital in the form of financing is banks. So, indirectly banks play an important role in environmental sustainability. This research aims to investigate the impact of green banking on financial inclusion and the growth of Islamic banking in Indonesia. The data analysis method employed is the Seemingly Unrelated Regression (SUR) method. The research approach is associative/quantitative, utilizing secondary data obtained and processed from annual reports and sustainability reports available on the official websites of the respective companies. Additionally, references from scientific journals and previous studies on selected Islamic banks are used. The sample includes PT. Bank Central Asia Sharia Tbk, PT. Bank KB Bukopin Syariah Tbk, PT. Bank Mega Syariah Tbk, PT. Bank Muamalat Indonesia Tbk, PT. Bank Panin Dubai Syariah Tbk, and PT. Bank National Retirement Savings Account Sharia Tbk, covering the period from 2019 to 2023.